Child Representation in Criminal Proceedings; Comparative Study between Malaysian Legal Framework and International Standards - Aminuddin, MUstaffa; Nazli, Ismail@Nawang; Mohd Badrol, Awang; Mohd Lotpi, Mohd Yusob (2017)
The right to a fair trial is a basic human right. One of the mechanisms used to safeguard to a fair trial is the right to counsel. The right to legal counsel is regarded as one of the most important and fundamental rights of any citizen. In the context of juvenile delinquency proceedings, assistance of counsel is essential to ensure children in conflict with the law get fair and just opportunity to challenge the criminal charge framed against them. This paper aims to examine the current Malaysian juvenile justice system on right of children to be represented in criminal proceedings in light of international standards. It will examine legal status and position of child representation at both pre-trial and trial stages of criminal proceedings under current Malaysian laws. It will also comparatively analyze to what extent current Malaysian laws on this aspect compatible with the standards set by the international instruments by analyzing statutory framework, court cases and legal practice. This study will attempt to identify loophole and imprecision of current Malaysian legal framework on child representation and accordingly provide possible recommendations that may be implemented towards domestication of international standards on this aspect into Malaysian juvenile justice system.